Impact of Poor Retention in HIV Medical Care on Hepatitis B Vaccination. (March 2015) - Franco, Ricardo A.; Tamhane, Ashutosh; Overton, Edgar Turner
Background: We identified factors associated with complete hepatitis B vaccination of patients with HIV. Methods: Retrospective analysis of patients undergoing HIV clinic orientation from 2000 to 2010. Vaccine-eligible patients had negative hepatitis B serologies at baseline. Receipt of at least 3 doses was defined as complete vaccination. Results: Of 1242 patients, 519 (42%) were completely vaccinated. Complete vaccination was positively associated with missing ≤25% of the visits during the first year of care (adjusted odds ratio [aOR] = 2.35, 95% confidence interval [CI]: 1.79-3.09), being naive to care (aOR = 1.50, 95% CI: 1.13-1.99), and living at the clinic's county (aOR = 1.33, 95% CI: 1.02-1.75). Complete vaccination was negatively associated with failure to remain in care >2 years (aOR = 0.18, 95% CI: 0.13-0.24), history of intravenous drug use (aOR = 0.48, 95% CI: 0.27-0.87), and baseline CD4 count <200 cells/mm 3 (aOR = 0.69, 95% CI: 0.53-0.92). Conclusion: Poor retention in HIV care is strongly associated with suboptimal hepatitis B vaccination.